Educational Transformation : Challenges and Opportunities in the Digital Era - Anita Candra Dewi; Wahyuddin Rahmad; Muh Syawaluddin; Nur Azizah; Reni Damayanti; Nur Amaliah Safitri (MultiTech Publisher, 2023)
Digital technology has completely changed the educational landscape, changing the way we learn, access information and interact with the world around us. The focus of the research that the author discusses is the challenges and opportunities in the digital era to face educational transformation. By using literature studies by conducting library studies to sharpen the analysis with the support of various sources that have theoretical connections. With the aim of finding out the challenges and opportunities in the digital era to face educational transformation.